The cultural-ecological mechanism of the urban space sustainable development by the view of the spatial perception logic - Ren, Yunying; Wu, Xiaochen; Chen, Chao (International Planning History Society Proceedings, 2018)
With the development of globalization the conflict between with the ecological carrying capacity and growth limits, the development of urban space is in the passive circulation with the Ecological capacity -Development limit and Social technology-Decision making at present. Undoubtedly, it is the essence of the sustainable development of human settlements either to passively deal with the development or the shrewd decision of cultural self-discipline beyond reality. On the one hand, with the improvement of technology and the strengthening of control ability, human consume natural resources, break through ecological capacity or resource limit and move towards alienation, namely, the constraint mode controlled by Ecological capacity-Development limit. On the other hand, urban space adapted to different periods of cultural, institutional, spiritual and material functional needs, but also restricted by the corresponding values and cultural concepts in the process of development and Self-renewal, it shows the self-discipline mode of seeking the harmony and balance between the ecology, society and economy. Correspondingly, urban space development is under the interaction of culture and ecology, society, economy and politics, thus forming the corresponding cultural ecological system, that is, the essence of sustainable development of urban space under the culture-ecology mechanism. The investigation introduces the concept of cultural ecology based on the interdisciplinary methods of cultural ecology, system dynamics and urban-rural planning, focuses on the integration of urban space cultural elements, constructs the cultural-ecosystem of urban space, and probes into the rational decision-making mechanism under the corresponding self-discipline mode under the view of Culture-Ecosystem, which included the basic attributes of urban space, urban space value attribute, as well as the urban spatial quality attributes, according to the spatial perception logic with the spatial perceptual attribute layer based on requirement hierarchy. And then based on the characteristics of cultural-ecosystem to explore the essence of sustainable development of urban space, which is a sort of adaptive development mechanism that can be discussed with the boundary conditions, the derivative mechanism and the space-time coupling. Which can be formed the cultural-eco self-discipline system to face with the challenge of the globalization.